Changes in call properties of Boana pulchella (Anura, Hylidae) in response to different noise conditions - Grenat, Pablo Raúl (2023)
The increasing expansion of urban areas leads to the emergence of new noisy environments that can affect animal communication. Calls play a crucial role in the mating displays of anurans, and the negative impact of anthropogenic noise-induced auditory masking has been reported in several species. We investigated the acoustic variation in 96 males (n=971 calls) of the treefrog Boana pulchella across acoustically undisturbed sites (AUS) and different noise conditions, associated with urban areas (URBAN) and roads (ROAD), in Central Argentina. We analyzed the effect of anthropogenic noise conditions on six temporal (call duration, intercall interval, first and second note duration, internote interval, call rate) and three spectral (dominant frequency of first and second note, frequency difference between them) call properties. The effects of temperature and size on acoustical variables were controlled. We observed differences in all call attributes among the noise conditions, except for intercall interval. Males exposed to URBAN and ROAD exhibited significant changes in call duration, dominant frequency of the second note, and frequency difference between them. URBAN males had longest internote interval, while ROAD individuals displayed increased first and second note duration and call rates. Interestingly, ROAD males exhibited immediate changes in call rate in direct response to passing heavy vehicles. Our study emphasizes the impact of anthropogenic noise on the acoustic characteristics of B. pulchella calls. Understanding how animals adapt to noisy environments is crucial in mitigating the adverse effects of urbanization on their communication systems. Future investigations should explore whether the observed call adjustments are effective in avoiding or mitigating the negative consequences of anthropogenic noise on reproductive success.